AFIKSASI FI'IL PADA HEADLINE BERITA PALESTINA-ISRAEL DALAM AKUN ALJAZEERA ARABIC: SHARAF (MORFOLOGI) - Nurhaliza, Yesi; Pribadi, Mohammad (STIQ Amuntai, 2024)
The language used every day cannot be separated from fi'il vocabulary or verbs as predicates in grammar. This research explains the process of verb affixation in Palestinian-Israeli news headlines. This qualitative research uses Palestinian-Israeli news headlines in Al Jazeera accounts as a data source. Data was collected through listening methods and note-taking techniques. The data that has been collected in an article is then analyzed using the collection method and the technique of selecting determining elements, followed by the technique of connecting and distinguishing. Researchers found verb affixations in Palestinian-Israeli news headlines, including prefixes found in fi'il mudhari', which are marked with the letters ي, ت, ا, ن. Second, suffixes are found in fi'il madhi, which are marked with the letters ا, و, ت, ن. Third, confixes are found in fi'il madhi and fi'il mudhari' which are marked with the letters ا, س, ت, ,ي at the beginning of the word and at the end of the word are marked with the letters .ا, ت, و, ن Fourth, infixes are found in fi'il madhi and fi'il amar which belong to the fi'il mazid group, which are marked with the letters ا and .ت